Review of the Use of Metals in Biomedical Applications: Biocompatibility, Additive Manufacturing Technologies, and Standards and Regulations - Leila Ladani; Michael Palmieri (Metals, 2024)
Advanced manufacturing techniques such as Additive Manufacturing (AM) have grown rapidly in major industries such as aerospace, automotive, and biomedical device manufacturing. Biomedical industry has benefitted immensely from AM because of its flexibility in design and its rapid production cycle. Powder bed processes are the major production technique for metal-based AM implants. This paper serves as a comprehensive review on the research efforts being made using AM to develop new patient centered medical devices. This review focuses on AM of the most common metals for biomedical applications, Magnesium alloys, Cobalt-Chromium alloys, pure Titanium, Titanium alloys. Several different aspects are discussed including biocompatibility and osseointegration, application of specific metals in different types of implants, their advantages and disadvantages, mechanical properties in comparison to bone, and their production technologies. Regulatory and quality assurance hurdles that are facing new innovations made using AM are discussed.